Mediasi Capital Adequacy Ratio pada Relasi Pengelolaan Aset dengan Maqashid Sharia Index - Habiburahman, Fadil; Ruhadi, Ruhadi; Sumiyati, Sumiyati (Jurnal Manajemen Bisnis dan Keuangan, 2024)
CAR is used as an indicator of financial health that helps banks manage risks effectively and prevent financial crises. With adequate CAR, banks can allocate assets efficiently according to sharia principles and still achieve profitability. This study aims to determine the mediation of the capital adequacy ratio in the relationship between asset management and sharia bank performance (maqashid sharia index) in sharia banking. The population in this study were 13 sharia commercial banks registered with the Financial Services Authority (OJK) in 2017 to 2022. The research sample was obtained from the entire population using a saturated sampling technique. The type of data used in this study is secondary data with a quantitative research method. Data analysis and testing of the research hypothesis used the Structural Equation Model Partial Least Square (SEM-PLS) method. The results of this study indicate that fixed asset turnover has no effect on the capital adequacy ratio, while total asset turnover has a significant effect on the capital adequacy ratio. Fixed asset turnover and total asset turnover have a significant effect on the maqashid sharia index, while the capital adequacy ratio has no effect on the maqashid sharia index in Islamic commercial banks. The results of this study indicate that the capital adequacy ratio cannot mediate the relationship between fixed asset turnover and total asset turnover with the maqashid sharia index.